Human-centred design processes for clinical decision support: A pulmonary embolism case study. (October 2020) - Babione, Julie N.; Ocampo, Wrechelle; Haubrich, Sydney; Yang, Connie; Zuk, Torre; Kaufman, Jaime; Carpendale, Sheelagh; Ghali, William; Altabbaa, Ghazwan
Highlights: Clinical decision support systems are the future - human-centred design facilitates. Our Pulmonary embolism tool showcases key benefits of human-centred design. This tool design captured important user needs other similar tools may have missed. Workflow support is achieved with interface consistency and multi-user support. Abstract: Background: Clinical Decision Support Systems (CDSS) can make patient care more efficient, cost-effective, and guideline-concordant. Many are created by clinicians who understand the challenges, but may publish concepts before considering subtle but important design details. Human-Centred Design (HCD) approaches provide necessary methods ensuring solid CDSS design. This article highlights HCD approaches in a pulmonary embolism CDSS case study context. Methods: This pulmonary embolism CDSS results from collaborative work between computer science, psychology, and medicine. HCD methods used include: evaluations of pre-clinical prototype recordings, iterative usability expert reviews with software refinement, formative usability testing, and (separately-published) clinical pilot study. Results: HCD methods were instrumental in iteratively creating an easy to use and functionally-sound CDSS. Retrospective evaluations revealed that participants spent considerable time on items that were out of order from natural cognitive diagnostic workflows. Features missing between original and study version were noted, confusing interface elements reworked, and currently-active decision tree branches were visually emphasized. From iterative usability reviews, positioning of information within the decision tree was radically reworked, information separated into levels of support for different user groups, and supportive versus directive language issues addressed. Formative studies identified issues such as interface adjustments and hospital workflow integration. Conclusions: Human-centred design approaches provide methods for integrating the skills and knowledge of many disciplines, illustrated by example in this pulmonary embolism CDSS creation. Advantages of leveraging many design guidelines as well as revealing new design considerations that would otherwise have remained hidden are described. The findings reported here support future CDSS design through HCD inclusion.